Follow me travel bag - Al-Sharief, Y.M.; Habaebi, Mohamed Hadi (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP) Bhopal (M.P.), India, 2019)
Follow Me Travel Bag is basically a smart bag to be used by travelers in away that provide them with additional features the normal travel bag does not. This bag will be empowered by a built-in tracking system that provide automatic self-control over the bag. It will integrate modern technology to provide easier usage of a travel bag, and enhance the security and movement issues. The main objective of this project is to ease the travel experience of individuals in handling their travel bags throughout their movement. This is accomplished by firstly making the bag following its owner without a need to drag it. Secondly, the bag will contain a location finder system to overcome the possibility of being lost, forgotten or stolen. This will solve the problem of losing the bag forever among with its contents which are valuable in much cases. This research is investigating the most suitable approach to achieve these targets though designing, controlling and testing of a smart programmable tracking system inserted in a travel bag.